(untitled) (Journal of Naval Architecture and Marine Engineering, 2025)
In this paper, a numerical study of the hydrodynamic performances of an autonomous unmanned vehicle (AUV) is proposed. For its propulsion, a model of a new seven-bladed propeller defined as stock propeller was created. Using FLUENT code, many numerical simulations were carried out, namely tests in open water, towing resistance and self-propulsion. This study is particularly focused on the thruster’s ability to perform its task correctly in view of a possible improved use. The examination of the propeller characteristics in open water test exhibits a better efficiency and the thrust can be improved by slightly adjusting the pitch distribution of the propeller. In the towing resistance test, wake behind the body was also investigated by studying axial velocity field in many transversal planes. Added to the self-propulsion test results, the evolution of the thrust magnitude in the wake by moving the thruster plane axially reveals that the required thrust level is reached far behind the actual position of the thruster disc. Therefore, the ratio of thrusts with or without the presence of the body is equal neither to unity nor to the ratio of torques. Journal of Naval Architecture and Marine Engineering, 22(1), 2025, PP. 63-80